Rental Price Decision of Shared Energy Storage Capacity Based on Supermodular Game - Yuqing WANG; Min ZHANG; Jiaxing WANG; Bohao LI; Tianyang YANG; Ming ZENG (Zhongguo dianli)
Under the background of construction of new power system, newly-constructed renewable energy stations are required to be equipped with energy storage system in many provinces in China. Shared energy storage capacity lease is a new model for renewable energy stations to meet the requirements with energy storage. However, its pricing mechanism is immature. In view of this, this paper proposes two energy storage allocation modes for renewable energy stations, namely self-construction and lease. Aiming at the competitive market of energy storage allocation composed of shared energy storage capacity leaseholders and energy storage equipment integrators, a decision model of shared energy storage capacity rental price based on supermodular game is constructed, which can solve the optimal price strategy of shared energy storage capacity lease under the equilibrium state of the market. A regional market with new energy stations equipped with energy storage system is used as an example to carry out pricing simulation. The results of the example have proved the effectiveness of the proposed model, which can provide a decision-making support for the price formulation and investment planning of shared energy storage.